Hypersensitivity in Chicken (Gallus gallus domesticus) due to the Association of Lidocaine and Bupivacaine in Neural-Guided Femoral and Sciatic Nerve Block - Silva, Helen Roberta Amaral da; Nunes, Newton; Gering, Ana Paula; Souza, Pâmilla Gabrielle Alexandre; Salgado, Karina Perehouskei Albuquerque; Ferreira, Obede Rodrigues; Nakamura, Amanda Jury; Guimarães, Anne Kaline da Silva (Acta Scientiae Veterinariae, 2021)
Background: Osteosyntheses, orthopedic surgeries that cause highly painful stimulation, are increasingly common in veterinary medicine. Epidural anesthesia is used to provide intraoperative and postoperative analgesia in mammals undergoing pelvic limb surgery. In birds, the synsacrum, the bone originating from the fusion of the lumbar and sacral vertebrae, makes this route inapplicable, thus peripheral nerve block is an easier option in this species. This report describes a case of local hypersensitivity following the association of lidocaine and bupivacaine in anesthetic blocks of the femoral and sciatic nerves in chickens (Gallus gallus domesticus). Case: A study was conducted in chickens evaluating the effectiveness of anesthetic sciatic and femoral nerve blocks, guided by a neural stimulator. Thirty-two 42-day-old male chickens of the species Gallus gallus domesticus, double breasted, weighing 1.86 ± 0.5 kg, were randomly divided into four groups: control (CG), lidocaine (LG), bupivacaine (BC) and the association of lidocaine and bupivacaine (LBG). The doses used were 4 mg/kg of 2% lidocaine and 2 mg/kg of 0.5% bupivacaine, without vasoconstrictor. For CG, 0.9% NaCl solution was used, respecting the total volume of 1 mL/kg. Only one bird from the LBG showed side effects, presenting sensory and motor loss for 24 h after the administration of these drugs, before euthanasia was performed using anesthetic induction with isoflurane through a face mask, followed by the intravenous administration of propofol and then potassium chloride. The chicken was submitted to a necropsy and macroscopically, soft, irregular, brownish lesions with a grayish focus were observed, indicating areas of necrosis in the muscles adjacent to the femoral and sciatic nerves. Histopathological examination showed mild, active inflammatory migration with perivascular organization, highlighting the presence of lymphocytes, plasmocytes, segmented heterophiles, and areas of hemorrhagic foci. The pairs of nerves evaluated showed edematous areas, but no inflammatory infiltrate, a histopathological finding that is considered to be nonspecific. Discussion: In the case of the chicken with side effects, histopathological examination showed vasculitis and hemorrhagic areas, which were correlated with ischemia and focal tissue necrosis, together with edematous lesions in the nerves evaluated, and extremities that showed an inflammatory response. These changes are related to acute hypersensitivity lesions, the drug response and drug hypersensitivity. Local anesthetics have been widely used in birds, but there are reports of reactions, including neurotoxicity and local myotoxicity, and bupivacaine is the drug that shows the highest cytotoxicity. However, long-term, repeated applications of bupivacaine on the sciatic nerve do not induce degenerative neural lesions in rats, rabbits, and dogs. The reactions described here are proportional to the concentration of the anesthetic injected, and in the case reported, the recommended dose for birds of 4 mg/kg of 2% lidocaine and 2 mg/kg of 0.5% bupivacaine, without vasoconstrictor, was adhered to. These findings suggest a reaction specific to the bird described; however, further studies regarding the local adverse effects of these anesthetics in birds should be conducted to make the practice of peripheral nerve block safer by testing different concentrations, associations and doses of the variety of drugs available. Keywords: birds, local block, drug hypersensitivity.